INFLUENCE OF INCONVENIENCE AND SERVICE QUALITY ON BRAND SWITCHING OF SERVICE PROVIDER IN MANADO - Tamon, Laurena R.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The more customers will satisfy the more amounts they will pay or they will feel unsatisfied and change the mobile service provider brand or called brand switching. Some factors that influencing the customers brand switching are inconvenience and service quality. The aim of this study is to know the simultaneous and partial influence of inconvenience and service quality on brand switching of mobile service provider in Manado City. This research used multiple regression analysis with sample of 100 respondents. The result shows that inconvenience and service quality are simultaneously and partially influence brand switching. Reason behind brand switching on service provider are like a late response of operator, activation of packages that take much time, late messages delivery, and there’s no update of packages activation. When the customers didn’tget the quality of service they’re expecting before the purchase makes the customer dissatisfied and this ends up in customer switch to other service provider. The mobile service provider should pay attention more about the quality of service and inconvenience to determine the major factors influencing for switching in this hyper competitive era, to retain the customer by providing value offer to keep them satisfy and to make customer loyal Keywords: inconvenience, service quality, brand switching